2016
DOI: 10.1080/00365521.2016.1186729
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of Zenker’s diverticulum with the stag beetle knife (sb knife) – feasibility and follow-up

Abstract: Flexible endoscopic treatment of ZD with the sb knife and overtube is effective, safe, and has lasting effects with a relatively low recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…In a retrospective study of 31 patients undergoing SB knife septal myotomy, 44 Battaglia et al described a median procedure time of only 14 min, with 83.9% of patients in symptom remission after a median follow up of 7 months. Efficacy and safety data were replicated by Goelder et al 59 (N = 52), who reported a low recurrence rate of 9.6% over 6 months, without complications of perforation or mediastinitis.…”
Section: Evolution Of Devicesmentioning
confidence: 83%
“…In a retrospective study of 31 patients undergoing SB knife septal myotomy, 44 Battaglia et al described a median procedure time of only 14 min, with 83.9% of patients in symptom remission after a median follow up of 7 months. Efficacy and safety data were replicated by Goelder et al 59 (N = 52), who reported a low recurrence rate of 9.6% over 6 months, without complications of perforation or mediastinitis.…”
Section: Evolution Of Devicesmentioning
confidence: 83%
“…Repici et al[29] for example required an average of 60 min for a flexible myotomy, Goelder et al[30] 32 min.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data, medical history and specifically prior treatments for ZD, anticoagulant or antiplatelet medication, clinical symptoms, and general health status were recorded. Symptoms were graded using the Augsburg symptom score dedicated to the ZD [10] and comorbid conditions with the Charlson Index [11]. Malnutrition was defined by a body mass index < 18.5 Kg/m² [12].…”
Section: Methodsmentioning
confidence: 99%